Use of climate and weather information by various agencies, meteorological institutions, and farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
CCAFS scientists and partners have developed participatory tools and approaches that enable organizations, such as national meteorolgical services, agricultural advisory services and NGOs, to provide information to large numbers of farmers, and support them to interpret and use the information in their agricultural planning. CCAFS research and capacity investment (with USAID, WMO, IRI and University of Reading) has supported the national meteorological services of Ethiopia, Tanzania and Madagascar to produce and deliver new historic and monitored climate information at a scale that is relevant to smallholder farmers, with complete national coverage. CCAFS efforts have to date influenced the policies and activities of organisations responsible for design and delivery of climate information and services in at least 10 countries in Africa, with beneficial impact reaching tens of thousands of farmers. Organizations which have taken up these approaches include the national meteorological services of Tanzania, Ethiopia, Madagascar, Malawi, Lesotho, Senegal and others; the AGRHYMET Regional Center in West Africa; and international organizations including the International Fund for Agricultural Development (IFAD), and the World Meteorological Organization (WMO).